A spirit of trust : a reading of Hegel's phenomenology - Brandom, Robert (The Belknap Press of Harvard University Press, 2019)
"In a new retelling of the romantic rationalist adventure of ideas that is Hegel's classic The Phenomenology of Spirit, Robert Brandom argues that when our self-conscious recognitive attitudes take Hegel's radical form of magnanimity and trust, we can overcome a troubled modernity and enter a new age of spirit."--Publisher's description